Pengaruh Lingkungan Kerja Dan Beban Kerja Terhadap Turnover Intention Pada PT Telkom Witel Bekasi - Afriliani S, Lidiya (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
PT Telkom Witel Bekasi is a company operating in the telecommunications sector and requires employees to achieve service targets at the end of each month. This study aims to examine the influence of Work Environment and Workload on Employee Turnover Intention. The research uses a quantitative approach with a survey method by distributing questionnaires. The sample consists of 33 respondents selected using a saturated sampling technique, where the entire population is used as the sample. Data were analyzed using data quality tests, classical assumption tests, hypothesis tests, and the coefficient of determination test, processed through SPSS version 27. The results show that partially, the Work Environment variable (X1) has a negative and significant effect on Turnover Intention (Y), with a t-value of -2.747 t-table 2.042 and a significance value of 0.01 0.05. Meanwhile, the Workload variable (X2) has a positive and significant effect on Turnover Intention, with a t-value of 5.333 t-table 2.042 and significance of 0.00 0.05. Simultaneously, both variables significantly affect Turnover Intention, with an F-value of 19.142 F-table 3.316. The R² value of 0.531 indicates that 53.1% of the variation in Turnover Intention is explained by the Work Environment and Workload variables.